Surface Modification of TiO2 Nanoparticles with Vitamin B12: Relationships between Vitamin B12 Content and Its Optical Properties. Issue 12 (19th November 2015) - Gharagozlou, Mehrnaz; Naghibi, Sanaz
Abstract: Anatase TiO2 nanoparticles (NPs) with particle size of 10–20 nm were prepared via sol gel technique. The as‐synthesized NPs were immerged in vitamin B12 (VB12 ) solutions with different concentrations. The in‐ fluences of the solution concentration on photoluminescence and photocatalytic activity of the modified NPs were studied. Fourier transform infrared spectroscopy (FTIR) results demonstrated that TiO2 NPs adsorb VB12 molecules and that a new band is formed at ∼2300 cm −1 . The VB12 loading process led to dimin‐ ishing of the aggregation of NPs and formation of a fibre shape structure. The best photoactivity and PL effect among the modified samples was related to sample 'd'. The optimum processing conditions to achieve this sample was found to be VB12 concentration of 5 g/L. Abstract : The vitamin B12 concentration is the factor exerting the influences on optical properties (photoluminescence and photocatalytic activity) of the modified NPs. FTIR results showed three new bands that are related to O=C=O and C–O stretching bands and their intensities increased by increase in vitamin B12 amounts. Modification with vitamin B12 leads to diminish the aggregation of the as‐synthesized NPs.